2003
DOI: 10.1107/s1600536803016726
|View full text |Cite
|
Sign up to set email alerts
|

Octane-1,8-diylbis[3-ethyl-1H-1,2,4-triazol-5(4H)-one]

Abstract: The title compound, C 16 H 28 N 6 O 2 , has a centre of symmetry. There are two planar 1,2,4-triazole rings, connected by an octane group. The crystal structure is stabilized by CÐHÁ Á ÁN, CÐHÁ Á ÁO and NÐHÁ Á ÁO intermolecular hydrogen bonds. Comment Schiff bases of 4-amino-1,2,4-triazole have received considerable attention over the past few decades (Kitaev et al., 1971; Mazza et al., 1976; Kargin et al., 1988). It is of interest that some of them are anti-in¯ammatory agents (Gupta & Bhargava, 1978) and new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…1 and 2, respectively. The geometrical parameters of both triazole rings are in very good agreement with literature values (Ç oruh et al, 2003;Zhu et al, 2000). The bond lengths and angles in the thienyl ring of molecule b are normal (Sommerer et al, 1998).…”
Section: Commentsupporting
confidence: 89%
“…1 and 2, respectively. The geometrical parameters of both triazole rings are in very good agreement with literature values (Ç oruh et al, 2003;Zhu et al, 2000). The bond lengths and angles in the thienyl ring of molecule b are normal (Sommerer et al, 1998).…”
Section: Commentsupporting
confidence: 89%
“…The C6 N1 bond is clearly a double bond, being much shorter than the other C-N bonds in the triazole ring. This distance is also comparable to literature data (Ç oruh et al, 2003;Yilmaz et al, 2005). The crystal structure features centrosymmetric dimers, formed by classical intermolecular N-HÁ Á ÁO hydrogen bonds, involving the amine functionality and the carbonyl of the triazole ring (Table 2).…”
Section: Commentsupporting
confidence: 89%
“…In a previous paper, we reported the synthesis and biological activity of new 1,2,4-triazol-5-one derivatives, in which different substituents were bound to N1 (Demirbaş et al, 2004). We and others (Ç oruh, Ustabaş et al, 2003;Zhu et al, 2000;Li et al, 2004) have also reported spectroscopic and structural data for some bis-1,2,4-triazole-5-ones and structures of 1,2,4-triazole systems with substituents in various positions on the triazole framework. These include 1-acetyl-4-(p-chlorobenzylidenamino)-3-methyl-4,5-dihydro-1H-1,2,4triazol-5-one (Ç oruh, Kahveci, Ş aşmaz, Ag ar & Kim, 2003), 1-acetyl-3-(p-chlorobenzyl)-4-(p-chlorobenzylidenamino)-4,5-dihydro-1H-1,2,4-triazol-5-one (Ocak et al, 2003) and 1acetyl-4-(p-chlorobenzylidenamino)-3-ethyl-4,5-dihydro-1H-1,2,4-triazol-5-one (Ç oruh, Kahveci, Ş aşmaz, Ag ar, Kim & Erdö nmez, 2003).…”
Section: Commentmentioning
confidence: 91%